Comparative study related to physico-chemical properties of four tomato cultivars grown in Kurdistan region, Iraq - Sidiq Aziz Sidiq Kasnazany; Luqman Gharib Karim Barznjy; Avan Assi Fatih; Avin Noori Mirza; Shex Jamal Jalal Krbchna (Kufa Journal for Agricultural Sciences)
This study was conducted to evaluate the physical, chemical and quality properties of four tomato cultivars Hawraman, Sktan, Kunara, and Krbchna, grown under a plastic house during 2021 in order to study growth, yield components, quality, and some phytochemical characteristics. A completely randomized block design  RCBD with three replications was followed in this study. The results showed the cultivar of  Hawraman obtained the maximum values of shape index, firmness, total sugar, ascorbic acid, and chlorophyll a with 1.520, 1152.440g, 1.880%, 39.031mg/100g FW, and 0.591 µg/ml FW, respectively. Sktan cultivar gave a higher value of a number of fruits per plant, yield per plant, juice, total carotenoids with (153.0 fruit plant-1, 6864.039g plant-1, 65.652%, and 0.532 µg/ml FW) respectively. Kunara cultivar achieved maximum values of a number of branches per plant, pH, TSS, TTA, chlorophyll b, and total chlorophyll with 13 branches plant-1, 5.470, 7.667%, 0.523%, 2.410 µg/ml FW and 2.693 µg/ml FW, respectively. While the Krbchna cultivar gave the maximum values of average fruit weight and size, polar and equatorial diameter, total phenolic and lycopene with 73.943g, 76.553 cm3, 64.450 mm, 48.537 mm, 84.684 mg/100g FW and 206.306 mg/100g FW respectively. While no significant differences in DM% and pectin% of tomato fruits were identified across all cultivars in this investigation.